European integration and inequality among countries: a lifecycle income analysis - Jose M. Pastor; Lorenzo Serrano (European Regional Science Association (ERSA), 2010)
We analyze the effects of the expansions of the European Union on inequality over the period 1960-2005 using an approach based on individuals' lifecycle incomes. This allows us to estimate permanent incomes and consider the effect of both survival rates and different rates of economic growth. According to our estimates, inequality in terms of permanent income was substantially less than that actually observed in current per capita income at the time of almost all the expansions (1973, 1981, 1986, 1995) except those of the last ten years (from 2004 onwards). The results point to the key role of policies that stimulate growth in the less developed countries. In fact, according to our estimates, with an annual β-convergence of 2% in current income, inequality in permanent income would be one third lower.
Keywords: 330; Inequality; Permanent Income; Convergence; Survival Rates; European integration; European Union